ENECSTASIS: A Tribute to an “Outrageous Proclamation” - Kanaris, Jim (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2023)
This paper is a tribute to a theologian and a biblical scholar who advocated for the central importance of subjectivity in academic inquiry, an especially “outrageous proclamation” nowadays. Among the many contributions of Bernard Lonergan (1904-1984), the theologian in question, the author focuses on Lonergan’s invitation to philosophy and theology to migrate from a basis in theory to a basis in interiority. The author opines that his strategy for doing this in religious studies, which he calls “enecstasis,” resonates with the hermeneutical strategy of his teacher, Sean McEvenue (1931-2018), the biblical scholar in question and student of Lonergan.